2016
DOI: 10.1071/rd13395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whole-body heat on male germ cell development and sperm motility in the laboratory mouse

Abstract: This study investigated the effects of high temperatures on male germ cell development and epididymal sperm motility of laboratory mice. In Experiment 1, adult males (n=16) were exposed to whole-body heat of 37-38°C for 8h day(-1) for 3 consecutive days, whereas controls (n=4) were left at 23-24°C. In Experiment 2, adult mice (n=6) were exposed to 37-38°C for a single 8-h period with controls (n=6) left at 23-24°C. Experiment 2 was conducted as a continuation of previous study that showed changes in spermatozo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The harmful effects of heat on spermatogenesis are well documented [ 49 ]. When testicles do not descend to the scrotal sac and remain within the abdomen—a condition termed cryptorchidism, the animal is sterile, although testosterone production is not affected [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The harmful effects of heat on spermatogenesis are well documented [ 49 ]. When testicles do not descend to the scrotal sac and remain within the abdomen—a condition termed cryptorchidism, the animal is sterile, although testosterone production is not affected [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other studies have suggested that also relatively moderate heat stress can induce DNA fragmentation within the testis (Gao et al 2012;Li et Capítulo 2: Heat stress effects on bovine sperm cells: a chronological approach to early findings 48 al. 2013; Wechalekar et al 2016). During the spermatogenesis process the most heat sensitive stages of germ cell development correspond to the spermatids and the pachytene spermatocytes Zhu et al 2004).…”
Section: Introductionmentioning
confidence: 99%